An efficient approach for the green synthesis of biologically active 2, 3-dihydroquinazolin-4(1H)-ones using a magnetic EDTA coated copper based nanocomposite. Issue 3 (11th January 2023) - Kohli, Sahil; Rathee, Garima; Hooda, Sunita; Chandra, Ramesh
Abstract : The fabricated catalyst Fe3 O4 @EDTA/CuI facilitates the synthesis of 2, 3-dihydroquinazolin-4(1 H )-ones under sustainable conditions with ideal values of green metrics in a short reaction time. Abstract : 2, 3-Dihydroquinazolinone derivatives are known for antiviral, antimicrobial, analgesic, anti-inflammatory, and anticancer activities. However, recent approaches used for their synthesis suffer from various drawbacks. Therefore, we have fabricated a highly efficient magnetic EDTA-coated catalyst, Fe3 O4 @EDTA/CuI via a simple approach. The ethylenediamine tetraacetic acid (EDTA) plays a crucial role by strongly trapping the catalytic sites of CuI nanoparticles on the surface of the Fe3 O4 core. The designed nanocatalyst demonstrates its potential for the catalytic synthesis of 2, 3-dihydroquinazolinones using 2-aminobenzamide with aldehydes as the reaction partners. The nanocatalyst was thoroughly characterized through X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), vibrating sample magnetometry (VSM), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), X-ray photoelectron spectroscopy (XPS) and inductively coupled plasma analysis (ICP). The physiochemically characterized nanocatalyst was tested for synthesis of 2, 3-dihydroquinazolinones and higher yields of derivatives were obtained with less time duration. Moreover, the catalytic synthesis is easy to operate without the use of any kind of additives/bases. Furthermore, the catalyst was magnetically recoverable after the completion of the reaction and displayed reusability for six successive rounds without any loss in its catalytic efficiency (confirmed by XRD, SEM, and TEM of the recycled material) along with very low leaching of copper (2.12 ppm) and iron (0.06 ppm) ions. Also, the green metrics were found in correlation with the ideal values (such as E factor (0.10), process mass intensity (1.10), carbon efficiency (96%) and reaction mass efficiency (90.62%)).